Microglia and macrophages contribute to the development and maintenance of sciatica in lumbar disc herniation. Issue 2 (7th June 2022) - Lu, Xuan; Chen, Lunhao; Jiang, Chao; Cao, Kelei; Gao, Zhihua; Wang, Yue
Abstract : Supplemental Digital Content is Available in the Text. Microglia and macrophages play an essential role in the development and maintenance of lumbar disc herniation–induced sciatica. Abstract: Lumbar disc herniation (LDH) is a major cause of sciatica. Emerging evidence indicated that inflammation induced by the herniated nucleus pulposus (NP) tissues plays a major role in the pathogenesis of sciatica. However, the underlying mechanisms are still elusive. Although microglia and macrophages have been implicated in nerve injury–induced neuropathic pain, their roles in LDH-induced sciatica largely remain unknown. This study successfully established and modified a mouse model of LDH. We found that nerve root compression using degenerated NP tissues can initiate remarkable and persistent sciatica, with increased and prolonged macrophage infiltration in dorsal root ganglia (DRG) and significant activation of microglia in the spinal dorsal horn. Instead, compression of the nerve root with nondegenerated NP tissues only led to transient sciatica, with transient infiltration and activation of macrophages and microglia. Moreover, continuous treatment of PLX5622, a specific colony-stimulating factor 1 receptor antagonist, ablated both macrophages and microglia, which effectively alleviated LDH-induced sciatica. However, mechanical allodynia reoccurred along with the repopulation of macrophages and microglia after the withdrawal of PLX5622. Using RNA sequencing analysis, the current study depicted transcriptional profile changes of DRG after LDH and identified several macrophage-related potential target candidates. Our results suggested that microglia and macrophages may play an essential role in the development and maintenance of LDH-induced sciatica. Targeting microglia and macrophages may be a promising treatment for chronic LDH-induced sciatica.